DarkASDNet: Classification of ASD on Functional MRI Using Deep Neural Network - Ahammed, Md Shale; Niu, Sijie; Ahmed, Md Rishad; Dong, Jiwen; Gao, Xizhan; Chen, Yuehui (Frontiers in Neuroinformatics, 2021)
The non-invasive whole-brain scans endure the aptitude to succor for diagnosing neuropsychiatric disorder diseases such as autism, dementia, and brain cancer. The assessable analysis for autism spectrum disorders (ASD) is rationally challenging due to the limitations of publicly available datasets. For diagnostic or prognostic tools, functional Magnetic Resonance Imaging (fMRI) exposed affirmation to the biomarkers in neuroimaging research because of fMRI pickup inherent connectivity between the brain and regions. There are profound studies in ASD with introducing machine learning or deep learning methods that have manifested advanced steps for ASD predictions based on fMRI data. However, utmost antecedent models have an inadequacy in their capacity to manipulate performance metrics such as accuracy, precision, recall, and F1-score. To overcome these problems, we proposed an avant-garde "DarkASDNet", which has the competence to extract features from a lower level to a higher level and bring out promising results. In this work, we considered 3D fMRI data to predict binary classification between ASD and typical control (TC). Firstly, we preprocessed the 3D fMRI data by adopting proper slice time correction and normalization. Then, we introduced a novel DarkASDNet which is surpassed the benchmark accuracy for the classification of ASD. Our model's outcomes unveil that our proposed method establish state-of-the-art accuracy of 94.70% to classify ASD vs. TC in ABIDE-I, NYU dataset. Finally, we contemplated our model by performing evaluation metrics including precision, recall, F1-score, ROC curve, and AUC score, and legitimize by distinguishing with recent literature descriptions to vindicate our outcomes. The proposed DarkASDNet architecture provides a novel benchmark approach for ASD classification using fMRI processed data.